Destination Branding Provinsi Nusa Tenggara Timur Melalui ‘The New Tourism Territory” - Ara, Roky Konstantin; Seran, Herman Elfridus; Jelahut, Felisianus Efrem (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
The purpose of this research is to find out how the implementation of the Destination Branding "The New Tourism Territory" stage is carried out by the East Nusa Tenggara Tourism Office. This study uses a qualitative research method using a case study approach. The results of the study show that 1) In implementing Destination Branding through "The New Tourism Territory" East Nusa Tenggara Province has carried out the five stages of destination branding proposed by Morgan, Pritchard and Pride, namely market investigation, analysis and strategic recommendations; brand identity development; brand launch and introduction; brand implementation; and monitoring, evaluation and review. 2) Brand Identity Development carried out by the Tourism and Creative Economy Office of East Nusa Tenggara Province, namely forming a destination identity, which is the characteristic of the Komodo dragon and "The New Tourism Territory is the new identity of the Province of NTT. 3) Brand Launch and Introduction carried out by the Office of Tourism and Creative Economy of East Nusa Tenggara Province through advertising, direct selling in international tourism exhibitions, tourism magazines, brochures, pamphlets, websites, Instagram, Facebook and events. 4) Brand Implementation carried out by the Office of Tourism and Creative Economy of East Nusa Tenggara is to apply the brand to promotional media, creating tourism products in the form of cultural events and attractions. 5) Monitoring, evaluation and review carried out by the Office of Tourism and Creative Economy of East Nusa Tenggara Province is a review of the use of promotional media as a communicator for the branding of "The New Tourism Territory", in this case the dispar.ntt website.